Village Baseline Study: Site Analysis Report for Kagera Basin – Rakai, Uganda - Onyango, Leah; Mango, Joash; Zziwa, A.; Kurui, Zena; Wamubeyi, B.; Sseremba O; Asiimwe, J. (2012)
The village baseline study of Kyengeza village in the CCAFS site Kagera Basin – Rakai in Uganda took place from 4 to 6 July 2011. Study participants are aware that their food security depends on protecting and appropriately managing natural resources. Nonetheless, there is a general decline in the state of natural resources such as rivers, lakes and forests, and the current use of the same resources is not sustainable over time. The main drivers of such changes in the region are population growth and government policies that have privatised forests and other natural areas previously managed by the village, effectively disempowering the community. There are more organisations operating beyond the locality than those operating in the community. The external organisations started delivering food, tools, medicines and other resources in response to HIV/AIDS. Their ability to mobilise resources, however, is undermining self-help capacity within the village, which is not conducive to sustainable rural development. Radio and organisations are the most frequently used sources of information for agricultural decision- making. There is a relatively active information network compared to other CCAFS sites, and a fair amount of consultation with all kinds of sources of information. This may be linked to high levels of uncertainty associated with climate change and food security.